LEGALISASI GANJA MEDIS (ANALISIS PUTUSAN MK NOMOR 106/PUU-XVIII/2020) - ERIK DWI PRASSETYO (Yuriska: Jurnal Ilmiah Hukum, 2022)
Indonesia is a state of law, the basic law for all laws and regulations in Indonesia is the 1945 Constitution of the Republic of Indonesia. In an effort to uphold the constitution and the principles of a democratic rule of law, the Constitutional Court has the authority to examine laws on the 1945 Constitution of the Republic of Indonesia. to find out how the judges of the Constitutional Court considered the decision Number 106/PUU-XVIII/2020 and to find out the impact of the decision. This study uses a normative juridical approach with a descriptive analytical method which will explain the description of the analysis of the data that has been collected. Based on the results of the research on Decision Number 106/PUU-XVIII/2020, it can be concluded that the judge in his decision had careful considerations such as looking at the facts contained in the trial and considering the results of the examination of related parties. The impact of this decision is that the public is prohibited from using class I narcotics for health services. The use of narcotics is only allowed within the scope of the development of science and technology. There is a strong impetus for research on the use of class I narcotics in the government and the private sector.Keywords: Judge's Consideration, Impact of Decision Number 106/PUU-XVIII/2020.